1993
DOI: 10.1128/jb.175.17.5648-5654.1993
|View full text |Cite
|
Sign up to set email alerts
|

A cryptic promoter in the O(R) region of bacteriophage lambda

Abstract: A cryptic promoter, designated P alpha, initiates transcription within the O(R) region of bacteriophage lambda. Transcription from P alpha proceeds in the direction of the cI repressor gene from sites 46 and 48 bp preceding the PRM transcription start site. P alpha is likely to compete with both PR and PRM for formation of open complexes, since it is only active when PR is mutated and can be suppressed by mutations that increase PRM activity. In addition, transcription initiation at P alpha is blocked by lambd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The times of 5 and 60 min refer to the duration of the incubation of DNA and RNA polymerase prior to initiation of RNA synthesis. In the lanes labeled P R Ϫ , note the appearance of a larger transcript, which likely originated at the P␣ promoter described by Gussin and co-workers (22). two-polymerase complexes (i.e.…”
Section: Fig 1 the Sequences Of The Variants Used In This Workmentioning
confidence: 70%
See 4 more Smart Citations
“…The times of 5 and 60 min refer to the duration of the incubation of DNA and RNA polymerase prior to initiation of RNA synthesis. In the lanes labeled P R Ϫ , note the appearance of a larger transcript, which likely originated at the P␣ promoter described by Gussin and co-workers (22). two-polymerase complexes (i.e.…”
Section: Fig 1 the Sequences Of The Variants Used In This Workmentioning
confidence: 70%
“…We (1, 2) as well as Gussin and co-workers (3,4) have shown that the presence of the P R promoter has a negative effect on the ability of RNA polymerase to form open complexes at P RM . The use of P R mutants allowed Gussin's group to demonstrate that conversely, the presence of an RNA polymerase at P RM negatively affects the utilization of a (weakened) P R promoter as well (5).…”
mentioning
confidence: 82%
See 3 more Smart Citations